Ectopic Pancreas in Duodenal Wall Putatively Causal for Gastrointestinal Bleeding - O. V. Khlynova; L. G. Girfanova; A. A. Cheremin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim: Clinical description of an ectopic pancreas (EP) in the duodenal wall.Key points: Aberrant or ectopic pancreas is a congenital abnormality of pancreatic heterotopy into unrelated organs with no connection to the true pancreas. Asymptomatic EP often leads to its casual diagnosis due to background complications or concomitant gastrointestinal disorders. A 57 years-old patient was urgently admitted to a surgery unit with signs of gastrointestinal bleeding. Esophagogastroduodenoscopy (EGD), colonoscopy, abdominal CT without intravenous contrast failed to diagnose the source of bleeding. Following two months, MRI scanning with contrast revealed an atypical lateral formation on descending duodenum with the lobulous contour and structure corresponding to normal pancreatic tissue, as well as signs of chronic pancreatitis and a solitary cyst in the pancreatic body. EP in duodenal wall was diagnosed as a putative cause of gastric bleeding.Conclusion. In this clinical observation, duodenal haemorrhage is reported as a manifestation of previously asymptomatic aberrant pancreas. Capacity of MRI in EP diagnosis has been demonstrated.